Just a Tea Stall Girl: Lessons from India - Jane Birkbeck (Social Work & Society, 2005)
This article charts the learning of a female academic who travelled and volunteered in southern India during a sabbatical leave from her university. Opportunities to discover gender, race and class connections ranged from tea-stall conversations to academic symposia; from outings with impoverished Indian families to excursions with social justice organizations. The author explores topics that include dowry, politics, globalization, communalism, and poverty. To illustrate her learning, she draws on the work of such renowned Indian scholars as Ali Ashgar Engineer and Vandana Shiva.